Скляні чаші з оплавленим краєм вінець у черняхівській культурі: проблема походження - Щепаченко, В.І. (Археологія, 2023)
Статтю присвячено вивченню проблеми походження однієї з груп черняхівського скляного посуду — чаш із оплавленим краєм вінець. Метою дослідження є пошук імовірних центрів, що можуть претендувати на роль місця виготовлення таких виробів, у межах доступної сьогодні інформації про розвиток склоробного ремесла в черняхівській культурі та сусідніх римських провінціях. In the article a research devoted to the problem of origin of hemispherical glass cups with fire-rounded rims discovered within the Cherniakhiv culture area is presented. These finds may be compared to a certain extent to Western European vessels of Eggers 199, 202, 205-206 types or the so-called Bodenrippenschale and Faßschale (after G. Rau) as well as cups of Werbkowice and Weklice types according to T. Stawiarska. Although, the Cherniakhiv artefacts are quite diverse in terms of their ornamental design, they are very similar referring to their morphology as well as finishing and decoration techniques. This fact, besides their identical chronological position and the same distribution pattern allow considering the mentioned items as a single glassware group and assuming their common origin. The conducted investigation demonstrates that at the end of the late Roman time (stage C3) the Cherniakhiv glass cups with fire-rounded rims were an original typological group of vessels, which had no synchronous analogues outside their distribution area. Although, the products that are similar to them in the technological point of view, occurred earlier in European Barbaricum, Roman provinces and antique centres of the Northern Black Sea region as well as at the end of the late Roman time in the Crimea. Taking into account the typological uniqueness and chronology of the Cherniakhiv finds as well as the absence of similar glassware among the products of synchronous glass-making centres of the neighbouring Roman provinces, it can be assumed that the most likely place of their origin was the Komariv workshop. The glass cups with fire-rounded rims are considered one of the items produced in this workshop. The artefacts that have close parallels among Cherniakhiv cups are also known here. It is worth noting, that the geochemical composition of some Cherniakhiv items finds close analogues between raw material and glassworking waste from Komariv, which is further evidence in favour of this hypothesis. The Roman origin of the Cherniakhiv cups, due to their morphological difference and chronological asynchrony with technologically similar products of the Roman glass-working centers, seems unlikely to us. Nevertheless, despite certain morphological differences, some early types of Western and Northern European artefacts, as well as Roman provincial glassware could serve as prototypes for the Cherniakhiv finds.